THE IMPACT OF SHARIA BTN CREDIT AND INCOME FACTORS ON PUBLIC INTEREST IN HOME OWNERSHIP LOANS (KPR) - Dwi Suci Lestari (Syari'ah Economics, 2022)
The purpose of this study was to determine the effect of the BTN Syariah credit system and income factors on public interest in mortgage ownership of KPR. The object of this research is this research is BTN Syariah customers who use musharaka in ownership of KPR at Perum Sinar Garden Ciamis as many as 43 units. The research uses quantitative descriptive methods, meaning that the research tries to describe a symptom of current events and reveals data that has taken place without manipulating other variables without affecting the dependent variable according to real events. The results of the study inform that the BTN Syariah credit system and income factors have a positive effect on people's interest in using KPR. The BTN Syariah credit system and income factors can affect people's interest in using KPR by 82%, while the remaining 18% is influenced by other variables.